Chronic Intermittent Hypoxia-Induced Dysmetabolism Is Associated with Hepatic Oxidative Stress, Mitochondrial Dysfunction and Inflammation - Joana L. Fernandes; Fátima O. Martins; Elena Olea; Jesus Prieto-Lloret; Patrícia C. Braga; Joana F. Sacramento; Catarina O. Sequeira; Ana P. Negrinho; Sofia A. Pereira; Marco G. Alves; Asunción Rocher; Silvia V. Conde (MDPI AG, 2023)
The association between obstructive sleep apnea (OSA) and metabolic disorders is well-established; however, the underlying mechanisms that elucidate this relationship remain incompletely understood. Since the liver is a major organ in the maintenance of metabolic homeostasis, we hypothesize that liver dysfunction plays a crucial role in the pathogenesis of metabolic dysfunction associated with obstructive sleep apnea (OSA). Herein, we explored the underlying mechanisms of this association within the liver. Experiments were performed in male Wistar rats fed with a control or high fat (HF) diet (60% lipid-rich) for 12 weeks. Half of the groups were exposed to chronic intermittent hypoxia (CIH) (30 hypoxic (5% O2) cycles, 8 h/day) that mimics OSA, in the last 15 days. Insulin sensitivity and glucose tolerance were assessed. Liver samples were collected for evaluation of lipid deposition, insulin signaling, glucose homeostasis, hypoxia, oxidative stress, antioxidant defenses, mitochondrial biogenesis and inflammation. Both the CIH and HF diet induced dysmetabolism, a state not aggravated in animals submitted to HF plus CIH. CIH aggravates hepatic lipid deposition in obese animals. Hypoxia-inducible factors levels were altered by these stimuli. CIH decreased the levels of oxidative phosphorylation complexes in both groups and the levels of SOD-1. The HF diet reduced mitochondrial density and hepatic antioxidant capacity. The CIH and HF diet produced alterations in cysteine-related thiols and pro-inflammatory markers. The results obtained suggest that hepatic mitochondrial dysfunction and oxidative stress, leading to inflammation, may be significant factors contributing to the development of dysmetabolism associated with OSA.